The properties of agroecosystems - Conway, Gordon R.; East-West Environment and Policy Institute; Southeast Asian Universities Agroecosystem Network; SUAN Information Support Service; Ford Foundation; East-West Center (1987)
Agroecosystems may be regarded as true cybernetic systems whose goal is increased social value. This is achieved through a variety of strategies that combine different levels of productivity, stability, sustainability and equitability. Agricultural development thus involves making trade-offs between these properties. The point is illustrated by selected examples from agricultural history, including the origins of agriculture, manorial and modern western agriculture, and the Green Revolution in Indonesia. It is suggested that these properties may be used normatively as combined criteria for evaluating the performance of agricultural development programmes and projects.
Introduction -- Agroecosystems as systems -- Agroecosystem properties -- Factors affecting system properties -- Agricultural development -- Agroecosystem analysis and development.
Photocopy.
This document has been provided by EAPI as part of its SUAN Information Support Service. The goal of this service is to make current literature relating to human ecology and agroecosystems research available to scientists participating in the Southeast Asian Universities Agroecosystem Network. Partial funding for this service is provided by a Ford Foundation grant to the East-West Center.
Includes bibliographical references (pages 112-117)
Keywords: Agroecosystems; Agriculture